Pendampingan dan Penyiapan Akreditasi Sekolah/Madrasha bagi SMP Negeri 1 Semau Selatan - Hendrik A.E. Lao; Andrian Wira Syahputra; Yakobus Adi Saingo; Yoksan Edison Neno (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2024)
This training is to provide understanding to school principals and teachers about the importance of preparing school accreditation in order to improve the quality and quality of school education. The targets for this Community Service group activity are leaders, teaching staff and education staff at SMP Negeri 1 Semau Selatan. The activity was carried out for 2 days starting from 7 until 8 August 2023. The main material presented was to provide education through assistance regarding the School/Madrasha Accreditation system and procedures for SMP Negeri 1 Semau Selatan and provide practice/simulation regarding concrete steps in preparing School/Madrasha Accreditation for SMP Negeri 1 Semau Selatan. The method used in carrying out activities is Participatory Action Research (PAR). The PKM activities were applied with lecture activities and strengthened through FGD (Focus Group Discussion) discussions and questions and answers between presenters/stakeholders and participants. The number of participants who took part in the training was 35 teachers. The results of the training show that participants understand and mastery of the material regarding creditation, starting from the accreditation system and procedures, and the participants also practice directly the concrete steps in preparing all the documents required for school accreditation. The training participants were very enthusiastic about taking part in this activity because one of the factors is that the school will enter a reaccreditation period in the near future in 2023.Keywords: accompaniment; preparation; accreditationAbstrakPelatihan ini untuk memberikan pemahaman kepada kepala sekolah dan guru akan pentingnya penyiapan akreditasi sekolah demi meningkatkan mutu dan kualitas Pendidikan Sekolah. Sasaran dalam kegiatan kelompok Pengabdian Kepada Masyarakat ini yaitu para pimpinan, tenaga pendidik maupun kependidikan di SMP Negeri 1 Semau Selatan. Kegiatan dilaksanakan selama 2 Hari mulai tanggal 7 sampai dengan 8 Agustus 2023. Materi pokok yang disampaikan adalah, untuk memberikan edukasi lewat Pendampingan mengenai sistim dan prosedur Akreditasi Sekolah/Madrasha Bagi SMP Negeri 1 Semau Selatan dan memberikan praktek/simulasi mengenai langkah-langkah konkrit dalam mempersiapkan Akreditasi Sekolah/Madrasha Bagi SMP Negeri 1 Semau Selatan. Metode yang digunakan dalam pelaksanaan kegiatan yaitu Participatory Action Research (PAR). Kegiatan PKM tersebut, diaplikasikan dengan aktifitas ceramah dan dikuatkan melalui diskusi FGD (Focus Group Discussion) serta tanya jawab antara pemateri/stakeholders dengan peserta. Jumlah peserta yang mengikuti pelatihan sebanyak 35 orang guru. Hasil Pelatihan menunjukkan bahwa pemahaman dan penguasaan materi tentang kreditasi Mulai dari sistim dan prosedur akreditasi sudah dipahami oleh para peserta dan peserta juga mempraktekkan secara langsung langkah-langkah kongkrit dalam mempersiapkan semua dokumen yang dipersyaratkan dalam akreditasi sekolah. Para peserta pelatihan sangat antusias dalam mengikuti kegiatan ini dikrenakan salah satu faktor adalah sekolah sudah memasuki masa reakreditasi dalam waktu dekat ditahun 2023 ini.Kata Kunci: pendampingan; penyiapan; akreditasi